Analysis of Customary Law on the Occurrency of Divorce in the Osing Tribe of Banyuwangi - Maryuliyanto; Redyana Lutfianidha; Wahyu Setyo Nugroho; Ferika Nurfransiska (Britain International for Academic Research (BIAR-Publisher), 2023)
The aims of this article I to analysis of customary law on the occurrency of divorce in the osing tribe of Banyuwangi. The research method used empirical research using qualitative descriptive. The result of the Marriage is a sacred bond to unite two people who have a relationship or feeling of love as a gift that must be grateful for. Kemiren Banyuwangi Village is a district that has a diverse society and has different cultures for each region and tribe, one of which is marriage traditions. The marriage tradition of the Osing tribe of Kemiren Village, Banyuwangi, includes cultural heritage from ancestors that still exists and is preserved today. Marriage in the Osing tribe is not only aimed at forming a harmonious, peaceful and peaceful household in society, but also to achieve physical and spiritual well-being. Therefore, in the Osing Tribe's traditional legal concept, marriage not only binds the married husband and wife but also strengthens the relationship between two families.